Memorias del VII Encuentro Escénico: “Manuel Zapata Olivella: Tradición e Identidad” (2020)
Memories of the VII Scenic Meeting: "Manuel Zapata Olivella: Tradition and Identity", held virtually, due to the Covid19 pandemic, on September 17, 18 and 19, 2020, brings together the compendium, description and analysis of all the activities carried out in this meeting, which from the academic, pedagogical, researching, and creative, highlights and disseminates the scenic work at national and Latin American level, with the vindictive, intercultural and identity vision that Manuel Zapata Olivella proposed with his artwork and cultural management